The Reconstruction of Legal Protection Regulations for Tourists Based on Justice Value - Haris Budiman; Suwari Akhmaddhian; Rivan Maulana; Agus Susanto; Komm Pechinthorn (Unissula, 2026)
This research aimed to examine the legal protection available and to propose reconstruction of government regulations in legal protection for tourists in Mount Ciremai National Park in Indonesia based on the principles of justice. The methodology used was socio legal research analysis. The results showed that legal protection for tourists in Mount Ciremai National Park area was supported by Islamic law, specifically referenced in the Qur'an, Surah Al-Tawbah, verse 6, as well as by various Indonesian laws and regulations. These included Law on Tourism, Kuningan Regency Regional Regulation on Tourism Implementation, Majalengka Regency Regional Regulation on Tourism Implementation, and Law on Consumer Protection. Furthermore, the proposed reconstruction of government regulations included the inclusion of a new article in Law on Tourism. This article would hold tourism entrepreneurs legally accountable for any losses resulting from the negligence of service personnel or deficiencies in infrastructure at tourist attractions. The research outlined two key discoveries where regulations governing tourism were established under existing tourism laws. Although these laws provided legal protection for tourists, the regulations did not address compensation for losses caused by the mismanagement of tourist attractions. The inclusion of these provisions would significantly enhance the legal framework for safeguarding tourists.